Semi Intensive and Semi Biofloc Methods for the Culture of Indian White Prawn, Fenneropenaeus indicus in High-density Polyethylene Liner Ponds - Indra Effendy; Samy Al Deen; Sambhu Chithambaran (Bogor Agricultural University, Indonesia, 2016)
An experiment (triplicated) was conducted to assess the growth and production of Indian white prawn, Fenneropenaeus indicus in semi intensive and semi biofloc culture technique for a period of 120 days in polythene liner ponds (300 m2). Water exchange was done at 10% in semi intensive culture method (control) and zero water exchange was done in semi biofloc method (treatment). Soya hull and molasses were added as carbon sources to induce biofloc formation in treatment ponds. Post larvae (PL20) were stocked at the rate of 100/m2 in each pond and fed with a standard shrimp feed. Shrimp growth, physico-chemical parameters of water, bacteria, phytoplankton and zooplankton population, immune response and physical quality of shrimp were recorded during the period. Significant difference (p < 0.01) in shrimp growth (weight) was observed between control and treatment. Phytoplankton population and total haemocyte count were found to be increased and pathogenic bacteria population decreased in treatment ponds. Strong linear relationship was found between growth and biofloc content in treatment ponds. Shrimp grown in biofloc pond showed better colour and taste compared to control. Semi biofloc technique can be considered as an ideal culture method for bio secure production of white shrimp in semi arid lands.